Peningkatan Kreativitas Siswa melalui Model Project Based Learning pada Pembelajaran Tematik - Hasanah Hasanah; Desniarti Desniarti; Nurdiana Siregar (LITERATUS, 2022)
This study aims to determine the increase in student creativity after the implementation of learning with the Project based Learning model and to see the interaction between initial abilities and learning to increase student creativity. The type of research used was a quasi-experimental with a sample of 25 students in class 5A in the experimental class and 29 students in class 5B in the control class. The instrument used is the observation sheet of student creativity. The instrument was prepared based on indicators of student creativity as many as 25 statements with four alternative answers. Data were obtained by observing using observation sheets of student creativity for all research samples. The data obtained were analyzed with two-way ANOVA. The results showed that (1) the increase in the creativity of students who received learning using the Project based Learning model was higher than students who received conventional learning in thematic learning (2) There was no interaction between initial abilities and learning towards increasing student creativity in thematic learning.